Studies on mosquitoes (Diptera: Culicidae) and anthropic environment: 2 - Immature stages research at a rice irrigation system location in South-Eastern Brazil - Forattini, Oswaldo Paulo; Kakitani, Iná; Massad, Eduardo; Marucci, Daniel (Revista de Saúde Pública, 1993)
A relation between a rice irrigation system and mosquito breeding was established in a study undertaken at the Ribeira Valley Experimental Station, from January through December 1992. Flooding favoured Anopheles (Nyssorhynchus) and Culex (Melanoconion) species, while empty paddies condition were propitious to Aedes scapularis and Culex (Culex) species. Compared with a more primitive area of the same region, several species showed high a degree of adaptation to the anthropic environment. Among them, Anopheles albitarsis, a potential malaria vector that breeds in the irrigation system, has shown immature stage production thirteen times higher than at the natural breeding sites. In addition, Ae. scapularis, An. oswaldoi, Cx. bastagarius, and Cx. chidesteri presented high levels of synanthropy.